2005
DOI: 10.1089/clo.2005.7.8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous DNA Methylation Status of the Regulatory Element of the MouseOct4Gene in Adult Somatic Cell Population

Abstract: The transcription factor Oct4 is specifically expressed in the germ line and pluripotent stem cells, and is indispensable for normal mouse development. To understand the epigenetic control of Oct4 expression, we examined the DNA methylation pattern of the Oct4 regulatory element in various types of cells. Bisulfite analysis showed that the regulatory element was unmethylated in P19 embryonal carcinoma cells, which robustly express Oct4. By contrast, the regulatory element was distinctly methylated in somatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…However, the CpG sites of the Oct4 PP in NSCs, where Oct4 is repressed, were partially methylated (male) or even highly methylated (female). The DNA methylation pattern of Oct4 is both variable and heterogeneous among the somatic cell population [21]. The methylation rate on the PE is also slightly higher in female (41.8%) than in male NSCs (32%) (unpublished data); however, this is an insignificant finding, as the opposite is found in certain female versus male somatic cell populations (data not shown).…”
Section: /Rosa26mentioning
confidence: 94%
See 1 more Smart Citation
“…However, the CpG sites of the Oct4 PP in NSCs, where Oct4 is repressed, were partially methylated (male) or even highly methylated (female). The DNA methylation pattern of Oct4 is both variable and heterogeneous among the somatic cell population [21]. The methylation rate on the PE is also slightly higher in female (41.8%) than in male NSCs (32%) (unpublished data); however, this is an insignificant finding, as the opposite is found in certain female versus male somatic cell populations (data not shown).…”
Section: /Rosa26mentioning
confidence: 94%
“…In contrast, the PE is required for Oct4 expression in postimplantation embryos and in EC cells [10]. The PE, however, has been shown to mediate the repression of Oct4 expression upon retinoic acid-induced cell differentiation [21] and is needed for correct downregulation of Oct4 expression [22].…”
Section: Distinct Reprogramming Of Endogenous and Exogenous Oct4mentioning
confidence: 99%
“…28 Hence, the promoters are hypomethylated in pluripotent cells, where the transcription factors are highly expressed, and become hypermethylated in differentiated/somatic cells, where the factors are silenced. [29][30][31][32] In a more recent study, a major DNA methylation change was observed in mouse embryos during the implantation and specification of the epiblast. In the epiblast, DNA methylation was found to target the promoters of lineage-associated genes, which are destined to be demethylated during terminal differentiation.…”
Section: Oct4mentioning
confidence: 97%
“…1C). Taking the developmental stage and tissue-specific methylation profiles of each CpG site of the oct4 PE/promoter regions into account (Gidekel and Bergman, 2002;Hattori et al, 2004;Marikawa et al, 2005), there is a possibility that temporal differences in the methylation of each CpG site results in the recruitment of different of transcription factors and regulate quantitative oct4 expression during ES cell differentiation. Many factors that regulate oct4 gene expression have been identified; however, the sequential and quantitative regulation of oct4 gene expression during ES cell differentiation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activity of oct4 is closely related to CpG island methylation. Oct4 expression is known to decrease and its CpG islands in the DE/PE/promoter regions are known to be increasingly methylated as differentiation progresses (Feldman et al, 2006;Gidekel and Bergman, 2002;Hattori et al, 2004;Marikawa et al, 2005). As mentioned above, numerous factors that regulate oct4 gene expression have been identified; however, knowledge of the regulatory mechanisms in relation to CpG island methylation and CpG island binding factors is very limited (Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%